Technical-tactical preparedness of the team "Helios" of Kharkov in the 25th football championship of Ukraine in the first league - Sergey Zhurid (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to define model characteristics of technical-tactical preparedness of the team, that participated in the championship of Ukraine of the first league for the purpose of the further improvement and correction of the educational-training process. Material & Methods: the researches were carried out by means of the method of expert estimates. Results: average values of the registered sizes for 16 games are analyzed. Various technical-tactical actions and their differences for the first and second times, and also separate indicators of a game of players and the team "Helios" of Kharkov are analyzed. Conclusions: quantitative and qualitative indicators (defect coefficient) as on team technical-tactical actions, and separately on each technical-tactical technique for every period of a game are received.